Investigation of stimulate brillouin scattering for the generation of millimeter wave for radio fiber system - 618598 Sevia Mahdaliza Idrus Sutan Nameh; Fakulti Kejuruteraan Elektrik (Skudai : Penerbit Universiti Teknologi Malaysia, 2007)
PSZJBL